INDUCTION OF SPAWNING IN THE TROPICAL WALKING CATFISH (Clarias batrachus) BY CONTROLLING WATER LEVEL AND TEMPERATURE - M. ZAIRIN JR.; K. FURUKAWA; K. AiDA (BIOTROPIA, 2001)
This experiment was carried out to confirm  the role of water level  and water temperature in inducing the spawning of tropical walking catfish. Mature males and females reared under 23 - 25 °C, were paired and induced to spawn by controlling water level and water temperature. Decreasing water level and returning it to its original level resulted in a low spawning rate (less than 6.7 %) at 23 °C. Decreasing water  level with simultaneous increase in water temperature, followed  by returning the respective levels to their originals gave high spawning rates (41.7 — 50 %); whereas the same treatment but without any water temperature decreased when the water level was returned to the initial level, gave a low spawning rate (16.7 %). Increasing water level only, failed to induce spawning. A high spawning rate was obtained also when changes in water level were carried out under high temperature of 28 °C. No fish spawned in the absence of the environmental stimulation. From the results, it is confirmed that water level and temperature play important roles in inducing spawning of tropical walking catfish. Changes in water temperature probably increase the sensitivity of fish to the change in  water level. Prolonged  exposure to high  water temperature could  also improve the sensitivity of fish. Key words: Walking catfish / spawning / water level / water temperature